Decrease in Body Weight and Liver Weight of Pups in Swiss Albino Mice by Spearmint Leaves Extract - Asma Zulfiqar, Sitwat Amna, Asma Siddique, Saqib Mansoor, Uzma Ali, Kanwal Sharif, Muhammad Suhail (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the effects of spearmint leaves extract on body weight, liver weight and RTWI of pups in Swiss albino mice. Study Design: Experimental study Place and Duration of Study: Anatomy Department, Shaikh Zayed PGMI, Lahore from 1st March 2014 to 30th June 2014. Methodology: Seven male and 21 female mice were used. After conception female mice were divided into control (A), low dose (B) and high dose (C) experimental groups. There were7 mice in each group. Group A was given distilled water where as group B was given 3g/kg/day and group C were given 6g/kg/day spearmint leaves extract. After 21 days (duration of pregnancy in mice) hysterotomy was done after euthanasia. Three groups of pups were made. These pups were selected randomly and marked as control, low dose and high dose experimental groups (A1, B1 & C1 respectively). Their body weights and liver weights were taken and recorded. Results: Body weight, weight of liver and RTWI of pups in both the experimental groups were decreased significantly with p<0.001 and difference between the experimental groups was also highly significant with p<0.001. Conclusion: The spearmint leaves extract decrease the body weight, weight of liver and RTWI of pups of Swiss Albino mice. Keywords: Spearmint, Garden mint, Herbal tea, Swiss Albino mice, Conception, Body weight, Weight of liver, RTWI